BANTUAN LUAR NEGERI ADB DALAM COREMAP-CTI FASE III UNTUK KONSERVASI LAUT INDONESIA - Panjaitan, Meta Janviena; Trisnaningtyas, Januari Pratama Nurratri (Global and Policy Journal of International Relations, 2023)
Indonesia is a country that is rich in natural resources, especially marine ecosystems. Currently, this ecosystem is under threat of being damaged due to various factors that have made ADB as a multilateral financial institution in the Asian region participate in supporting marine conservation to boost Indonesian economy. In fact, the marine ecosystem has a big impact, such as contributing 3.7% of Gross Domestic Product (GDP) and has the potential to contribute 1.3 times that amount. By using a qualitative descriptive research method and using concepts related to International Relations, namely Environmental Conservation and Foreign Aid, author will explain and elaborate that the form of ADB's foreign aid to Indonesia in COREMAP-CTI Phase III are financial assistance and technical assistance. The COREMAP-CTI program which has been carried out in three phases has produced significant results for the development of marine ecosystems. Thus, ADB's foreign aid to Indonesia is considered quite significant in marine conservation in Indonesia.DOI: https://doi.org/10.33005/jgp.v11i01.3980